Dendrimer-based nanotherapeutics - Kesharwani, Prashant (Academic Press, 2021)
Dendrimer-Based Nanotherapeutics delivers a comprehensive resource on the use of dendrimer-based drug delivery. Advances in the application of nanotechnology in medicine have given rise to multifunctional smart nanocarriers that can be engineered with tunable physicochemical characteristics to deliver one or more therapeutic agent(s) safely and selectively to cancer cells, including intracellular organelle-specific targeting. This book compiles the contribution of dendrimers in the field of nanotechnology to aid researchers in exploring dendrimers in the field of drug delivery and related applications. This book covers the history of the area to the most recent research. The starting chapter covers detailed information about basic properties about dendrimers i.e. properties, nomenclature, synthesis methods, types, characterization of dendrimers, safety and toxicity issues of dendrimers. Further chapters discuss the most recent advancements in the field of dendrimer i.e. dendrimer-drug conjugates, PEGylated dendrimer, dendrimer surface engineering, dendrimer hybrids, dendrimers as solubility enhancement, in targeting and delivery of drugs, as photodynamic therapy, in tissue engineering, as imaging contrast agents, as antimicrobial agents, advances in targeted dendrimers for cancer therapy and future considerations of dendrimers. Dendrimer-Based Nanotherapeutics will help the readers to understand the most recent progress in the field of dendrimer-based research, suitable for pharmaceutical scientists, advanced students, and those working in related healthcare fields.